Improvement method for calculation gate circuit insulation monitoring 3B with measuring relay consisting of two coils - Харитонов, Александр Александрович; Ликаренко, Анатолий Григорьевич; Мельник, Ольга Евгеньевна; Ляхова, Надежда Николаевна (Technology audit and production reserves, 2014)
Efficiency of electrical breaker is identified with the level reached in their risk of electric shock, and this level is determined by the following parameters. The first - a line of protective characteristics circuit breakers electrical safety requirements, the second - the ability to retain this correspondence for all occurring negative impacts of factors of production, and the third - the ability to provide a functional interaction, members of the circuit breakers leakage relay and power switching device network. The second and third parameters are determined on the basis of compliance with the requirements of the circuit breakers imposed operating conditions of mining production. The paper presents an improved method of calculating the gate control circuit with two-winding insulation 3B measuring relays. In the research proposed a new method of calculation and the optimization of circuit parameters the automatic control of isolation ACI-380 in order to increase its sensitivity from 0.33 to 0.63 mA/com in the same functional characteristics.The results of the research will enhance the reliability of the relay leakage, thereby improving the protection of persons against electric shock in LV networks with isolated neutral and will reduce the likelihood of ignition of fire-damp and coal dust leakage current.